2021
DOI: 10.1007/s11431-020-1727-0
|View full text |Cite
|
Sign up to set email alerts
|

Initial scalar lithospheric magnetic anomaly map of China and surrounding regions derived from CSES satellite data

Abstract: The China Seismo-Electromagnetic Satellite (CSES), China's first satellite to measure geophysical fields with scientific goals in both space and solid earth physics, was launched successfully in February 2018. It carries high-precision magnetometers to measure the geomagnetic field. In this study, the CSES magnetic data were used to extract the signal of the lithospheric magnetic field caused by magnetized rocks in the crust and uppermost mantle. First, an along-track analysis of the CSES magnetic data was und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Based on international standards [Wang et al, 2021a], the numerical values of ground surface acceleration (𝛾)…”
Section: Xiuwen Wu and Daoyun Linmentioning
confidence: 99%
“…Based on international standards [Wang et al, 2021a], the numerical values of ground surface acceleration (𝛾)…”
Section: Xiuwen Wu and Daoyun Linmentioning
confidence: 99%
“…2023, 15, 4578 2 of 11 work together to provide magnetic field measurements from DC to ~15 Hz. Previous scientific studies have shown very good usability of the magnetometer data [7][8][9]. In-flight calibration based on the CDSM's scalar data is in principle well established and the quality is already very good.…”
Section: Introductionmentioning
confidence: 96%
“…Data from the ESA's Swarm satellite constellation (2013−), which comprises three identical satellites (Friis-Christensen et al, 2006), has facilitated creation of various high-quality lithospheric field models (ThĂŠbault et al, 2016;Olsen et al, 2017). The CSES (China Seismo-Electromagnetic Satellite, 2018-) is designed to facilitate earthquake studies and to measure geophysical fields, supporting scientific goals of both space and solid earth physics (Shen XH et al, 2018;Huang JP et al, 2018); its scalar magnetic data have been used for lithospheric magnetic anomaly identification and modeling (Wang J et al, 2021(Wang J et al, , 2023a. In May 2023, a new Chinese satellite aiming at monitoring geomagnetic changes, the Macao Science 1 satellite (Zhang K K, 2023), was launched.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the more striking magnetic anomalies around the world, the long-wavelength magnetic anomalies in China and surrounding regions are much weaker, with maximum amplitudes of about 5 nT at 500 km altitude (Figure 2). Thanks to high-resolution magnetic measurements and mature modeling methods, many researchers have begun to notice these magnetic anomalies and have done general analyses using geological and tectonic data (An ZC et al, 1992;Zhang CD, 2003;Kang GF et al, 2010;Ou JM et al, 2013;Du JS, 2014;Gao GM et al, 2018;Wang J et al, 2020aWang J et al, , 2023a. However, specialized research on these weaker anomalies has been quite inadequate to clarify their geological origins or to facilitate further tectonic applications.…”
Section: Introductionmentioning
confidence: 99%